Mucocele: A Case Report - Dhananjay B Ghunawat; Seema Marathe; Sanjay G Thete; Sheen Chakraborty; Harshita Lath; Namrata Vilas Shehare; Rashmi Laddha (Wolters Kluwer Medknow Publications, 2024)
Mucoceles are the most common minor salivary gland disorder and represent the second most frequent benign soft tissue tumors of the oral cavity, following irritative fibroma. Various treatment modalities have been suggested for mucocele among which different types of lasers being the most recent and advanced. In the present case reports, diode laser was used for the excision of mucocele on the lower lip, and the advantages of it over the conventional scalpel method were minimal discomfort, bleeding, recurrence, and better compliance among patients.